Creationism or Evolutionism: an Optimistic View of Evolutionism by Teilhard de Chardin” - Part II - Paul Rohan, J.C. (Sri Lanka National Seminary Journal, 2018)
When analyzing a reality, it is inevitable that one inquires about its origin. The question of origin is inherent in any comprehensive inquiry into the nature of realities. Up to the scholastic time, not only in religious beliefs but also for scientists and philosophers, creatio ex nihilo was an accepted sound and convincing theory to explain the origin of all things. It refers to creation of the entire universe out of nothing: not out of anything pre-existing. Thus creationism supplied a straightforward answer and explanation to the origin of realities. With the development of science, biblical and religious concept of the God as a creator was replaced by the theory of evolution in the modern era. The rationalistic, mechanistic and atheistic trends and the theory of evolution claimed that everything evolved from matter, even life and consciousness. This gave birth to the fiery debate whether creation or evolution is the valid theory to explain the origin of realities. There are however those who subscribe to the raison d'être for both creationism and evolutionism. Such thinkers were able to reconcile science and religion, faith and reason and did not recognize any contradiction between creationism and evolutionism. Pierre Teilhard de Chardin, a Roman Catholic priest of the Society of Jesus, both a geologist and a paleontologist, is one among those who held this view. He was able to present evolution as not contradicting a creator God, but saw in creationism and evolutionism the same fact of the origin of realities. He was thus able to develop a view which was commensurate with evolutionism which the religious community considered atheistic and heretic. This article therefore analyses this optimistic and wholistic view of evolution developed by Teilhard de Chardin by rationalizing the arguments presented by him for evolutionism versus creationism with an attempt to reconcile the two.
Keywords: Creatio ex nihilo; Darwinism; Big Bang; Hominization; Biosphere; Noosphere; Consciousness; Omega; Teleological; Christogenesis; Anthropogenesis